2015
DOI: 10.1167/iovs.15-17168
|View full text |Cite
|
Sign up to set email alerts
|

HLA Associations in a Cohort of Children With Juvenile Idiopathic Arthritis With and Without Uveitis

Abstract: We report the novel finding that carriage of HLA-DRB1*11 and *13 appears to increase the risk of uveitis in children with JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Interrogation of larger sample collections and extensive functional work in this region will be necessary to fully understand the mechanism(s) driving the association. Nevertheless, our findings indicate that, although JIA with uveitis and JIA without uveitis share clinical features and HLA‐specific genetic risk factors , there appear to be genetic signals that are specific to JIA with uveitis.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Interrogation of larger sample collections and extensive functional work in this region will be necessary to fully understand the mechanism(s) driving the association. Nevertheless, our findings indicate that, although JIA with uveitis and JIA without uveitis share clinical features and HLA‐specific genetic risk factors , there appear to be genetic signals that are specific to JIA with uveitis.…”
Section: Discussionmentioning
confidence: 61%
“…The relatively high frequency of serine 11 in the JIA patients who did not develop uveitis (Table ) indicates the likely involvement of additional (epi)genetic and environmental factors in uveitis. Only a handful of candidate gene studies , HLA‐specific analyses , and a recent GWAS have investigated uveitis as a phenotype separate from JIA overall, with the latter study identifying HLA–DRB1*1501 as a uveitis risk factor. Genes outside the MHC have also been implicated in JIA‐associated uveitis, including a polymorphism in VTCN1 and variants near the immune genes TRAF1 and C5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследование случай-контроль с участием 107 пациентов европеоидной расы с олигоартритом и РФ-негативным полиартритом показало связь носительства аллелей HLA-DRB1*11 и *13 с развитием увеита: ОШ 9,0 (95% ДИ 2,8-29,0) по сравнению со здоровыми лицами и ОШ 8,6 (95% ДИ 1,0-74,4) по сравнению с группой с изолированным ювенильным идиопатическим артритом [7]. В ряде работ, в том числе отечественных, показаны ассоциации HLA-А2 и HLA-DR5 / HLA-DRB1*11 с ранним началом олигоартрита у девочек и риском развития увеита [8].…”
Section: патогенезunclassified
“…Although previous studies have shown that uveitis develops most frequently early in the disease , there are very limited data about its precise risk during the course of JIA. The annual incidence (rate of occurrence of new cases in a given year) after JIA diagnosis is more informative about the risk of uveitis than frequency estimates over a reference period of time.…”
Section: Introductionmentioning
confidence: 99%